The Role of Social Media in Dissemination of Agricultural Information in Pustaka Bogor - Tamara Dwiyanti; Indira Irawati (Metakom, 2019)
This study focuses on the role of social media in disseminating agricultural information at Pustaka Bogor. Qualitative methods were used with a case study approach. Data collection is through observation and interviews with 3 (three) informants. Our findings indicate that the policies regarding the use of social media at Pustaka are based on the target audience of its library. The social media being used by Pustaka to disseminate information are Facebook, Twitter, Instagram, and Youtube. Social media plays an important role in the dissemination of information carried out by Pustaka. Our findings also support the Pustaka’s mission in disseminating information. Social media can help libraries to promote and disseminate information specifically in agriculture to community users.